Organic vapor sensing behavior of polycarbonate/polystyrene/multi-walled carbon nanotube blend composites with different microstructures. (5th October 2019) - Li, Yilong; Pionteck, Jürgen; Pötschke, Petra; Voit, Brigitte
Abstract: With the focus on the use as leakage detectors, the vapor sensing behavior of conductive polymer composites (CPCs) based on polycarbonate/polystyrene/multi-walled carbon nanotube (PC/PS/MWCNT) blends with different blend ratios was studied as well as their morphological and electrical properties. In the melt mixed blend composites, the MWCNTs are preferentially localized in PC. At the PC/PS ratio of 70/30 wt%, the composites showed a sea-island structure, while for blends containing 40 wt% or 50 wt% PS co-continuous structures were developed resulting in a reduction in the MWCNT percolation threshold. The saturated vapors of the selected solvents have good interactions to PS but different interactions to PC. At 0.75 wt% MWCNT, sea-island CPCs showed high relative resistance change ( R rel ) but poor reversibility towards moderate vapors like ethyl acetate and toluene, while CPCs with co-continuous structure exhibited lower R rel and better reversibility. All CPCs showed poor reversibility towards vapor of the good solvent dichloromethane due to strong interactions between polymers and vapor. In the vapor of the poor solvent cyclohexane, CPCs with higher PS content showed increased R rel . After extraction of the PS component by cyclohexane, the sensing response was decreased and the R rel of the co-continuous blend even reached negative values. Graphical abstract: Unlabelled Image Highlights: Vapor sensing response of immiscible conductive polymer blend composites was studied using different solvents The response of composites with 0.75 wt% MWCNT reached up to 1200% after 100 s immersion in saturated ethyl acetate vapor At given filler content, vapor sensing depends on the blend morphology type and the polymer-vapor interaction Sea-island structures show high resistance changes but poor reversibility, which is opposite for co-continuous structures The varied sensing behavior is caused by changed solvent vapor accessibility in different morphology types